Tatobi Panggang as a Postpartum Traditional Care of Timor Tribe in Bello Village - Kencanawati, Dewa Ayu Putu Mariana; Mirong, Ignasensia Dua; Bakoil, Mareta B. (Health Notions, 2018)
Fifty percent of maternal deaths occur within the first 24 hours of delivery. Furthermore, 30 percent of the population still practices traditional treatments for a mother in their postpartum period. Timor tribe in Nusa Tenggara Timur (NTT) has culturally distinctive practices for a mother in their postpartum period, called as tatobi and panggang. These two practices put the health at serious risk. For this reason the present research aims to further investigate such cultural practices of the Timor concerning the postpartum care (tatobi and panggang) in Bello village, Maulafa distric. This present research was qualitative employing phenomenological research design. The sample was determined by employing purposive sampling method. The results show that the mother, during their postpartum period, chose to do tatobi and panggang because such practices are believed to be able to help the mother for the post-pregnancy recovery. However, in the actual practices they often caused excessive bleeding leading to a higher risk of suffering from infections and postpartum anemia. Some conclusions can be drawn; such cultural practices, tatobi and panggang, are seriously risky for the postnatal mother, but they are beneficial, on the other hand, to improve blood circulation and promote exclusive breast milk. Keywords: Culture, Postpartum, Timor tribe